1999
DOI: 10.1021/jp9915477
|View full text |Cite
|
Sign up to set email alerts
|

A Quantum-Chemical Study of the C2H3F2+ and C2H3Cl2+ Isomers and Their Interconversion. CBS-QB3 Proton Affinities of Difluoroethenes and Dichloroethenes

Abstract: Potential energy surfaces of the C2H3X2 + isomers and proton affinities of dihaloethenes C2H2X2 (X = F, Cl) were computed at the B3LYP/6-31++G(d,p), MP2/6-311++G(d,p), and CBS-QB3 levels. The classical 1,1-dihaloethyl cations CH3CX2 + represent global minima for the C2H3X2 + isomers. Other minima located are classical 1,2-dihaloethyl cations, the chloroethylchloronium (Cl-bridged) cation, halogen-protonated cis-1,2-, trans-1,2-, and 1,1-dihaloethenes, and ion−dipole complexes of the CH2CX+ cation with the HX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…Hydride abstraction, which is the characteristic ionization process observed with alkanes and alkenes under our experimental conditions,11 is expected to be particularly favorable in the case of 1,1‐DCA due to the high stability of the 1,1‐dichloroethyl cation resulting from hydride removal from C‐1. In a recent quantum‐chemical study, the 1,1‐dichloroethyl cation was indeed found to represent the global minimum on the potential energy surface calculated for the C 2 H 3 Cl 2 + species 12. Similarly stabilized [M − H] + species are expected from 1,1,2‐TCA and 1,1,2,2‐TCA.…”
Section: Resultsmentioning
confidence: 83%
“…Hydride abstraction, which is the characteristic ionization process observed with alkanes and alkenes under our experimental conditions,11 is expected to be particularly favorable in the case of 1,1‐DCA due to the high stability of the 1,1‐dichloroethyl cation resulting from hydride removal from C‐1. In a recent quantum‐chemical study, the 1,1‐dichloroethyl cation was indeed found to represent the global minimum on the potential energy surface calculated for the C 2 H 3 Cl 2 + species 12. Similarly stabilized [M − H] + species are expected from 1,1,2‐TCA and 1,1,2,2‐TCA.…”
Section: Resultsmentioning
confidence: 83%
“…The process appears straightforward in the case of the ion derived from 1,1,1 , which should have the structure of the 1,1‐difluorotrichloroethyl cation ( g ) (Scheme ). The same species could also be formed from 1,1,1,2 via Cl loss from C‐2; in this case, however, the alternative Cl loss from C‐1 should be favored since the ionic product h is expected to be more stable than g in view of recently published data for the difluoro‐ and dichloroethyl cations 5. Finally, halogen transposition is necessarily implied in the CF 2 elimination from C 2 Cl 3 F 2 + ions deriving from 1,1,2 (Scheme ).…”
Section: Resultsmentioning
confidence: 98%
“…In the latter field, various ion‐etching techniques for microcircuit fabrication (ion milling, ion etching, sputter etching) should be mentioned, in addition to promising new technologies for the treatment of volatile organic compounds (VOCs) which make use of non‐thermal plasmas 3. In addition to the specific interest associated with the applied fields, fundamental knowledge is being actively pursued about the effects of substitution by halogens, notably fluorine and chlorine, on the structures, energetics and reactivity of simple carbenium ions and related species 4–6. Such knowledge is based on the results of experimental investigations which are often integrated with those of theoretical studies.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Outras propriedades muito estudadas são as afinidades por próton [17][18][19][20][21][22][23] e por elétron, [24][25][26][27] a acidez, 28 bem como a identificação da estrutura mais estável para um determinado isômero. 29,30 Compostos inorgânicos também podem ser explorados utilizando métodos compostos pelo cálculo do potencial de redução 31 em reações de óxido-redução.…”
Section: Introductionunclassified